المال المغصوب في ظل سقوط الحكومة المركزية الصومالية: دراسة فقهية ميدانية - فارح، إسمهان علي (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2019)
The research aims at shedding light on the worrying rise of extoration after the fall of the Somali Central Government. The research also proposes a set of solutions which may contribute to solving the occurring conflicts which have contributed to this criminal behaviour.The researcher depended on a methodology combining between the induction and analysis approaches. Opinions of classical and contemporary Islamic jurists to present provisions of extortion of money and its effects. She also depended on the historical and descriptive approaches to highlight the situation of the problem of the collapse of the Somali Central Government, and to indicate the reasons for its collapse as well as the reasons for the spread of money extortion phenomenon and its effects in the Somali society through using the findings of its questionnaire conducted in the capital Mogadishu. The study ended up with a set of results, mainly that the Islamic sharia fights and criminalizes extortion subjecting the perpetrator to penalty in the world before the Hereafter and that persons who committed money extortion have to return the illicit gains. It also indicates a number of reasons behind the spread of extortion of public and privatefunds in Somalia such as civil wars, lack of values of faith, brotherhood spirit, good example, spread of corruption in the society, disregard to the application of the Islamic sharia and solely depending on man-made laws which do not suit the Somali society. The researcher presented some suggestions containing political, social and religious solutions to bring about a more respectable modern Somali society.